Determinants of Motivation and its Implications on Employee Performance - Nazifah Husainah; Azimah Hanifah (Universitas Trisakti, 2021)
This research can be classified as explanatory research, which explains the causal relationship and the interrelationship of research variables that include wage earners and human resource audits of employee performance through employee work motivation. The population used in this study was 189 employees with a sample of 128 respondents. The data collection method in this study is through questionnaires through data contained in research objects both in primary. The analysis tool used in this study is path analysis, used to know the direct and indirect influence of free variables with variables bound through intervening variables. The free variables in this study are wages and human resource audits, variables tied to this study are employee performance, and the intervening variable is motivation. The results showed wages had a significant influence on the motivation. Human resources audit have significant effect on the motivation. In this study, there are analysis results that show insignificant results between wages and performance. Human resource audits has significant influence on performance.